2020
DOI: 10.1507/endocrj.ej20-0050
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of stem cells transplantation in patients with type 1 diabetes mellitus—a systematic review and meta-analysis

Abstract: Stem cells (SCs) therapy is a new promising therapeutic modality for type 1 diabetes (T1DM). We performed a systematic review and meta-analysis to evaluate the efficacy and safety of stem cells transplantation (SCT) in patients with T1DM. We searched five literature databases (MEDLINE, EMBASE, Web of Science, WanFang and CENTRAL) up to 31 October 2019. 29 studies (487 patients with T1DM) were included in our meta-analysis. There was no substantial publication bias. Meta-analysis showed the SCT had significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
(26 reference statements)
1
1
0
Order By: Relevance
“…Despite heterogeneity among the studies reviewed, our findings support an association between MSCs therapy and better glycemic control for T1D patients. This aligns with a recently published meta-analysis (Wu et al 2020 ), which reported a significant effect on reducing HbA1c levels and improving C-peptide levels among T1D patients after one year follow-up of SCT.…”
Section: Discussionsupporting
confidence: 91%
“…Despite heterogeneity among the studies reviewed, our findings support an association between MSCs therapy and better glycemic control for T1D patients. This aligns with a recently published meta-analysis (Wu et al 2020 ), which reported a significant effect on reducing HbA1c levels and improving C-peptide levels among T1D patients after one year follow-up of SCT.…”
Section: Discussionsupporting
confidence: 91%
“…It is di cult to clarify the validity and safety of iPSC treatment based on the limited number of clinical trials (i.e., NCT03403699) [7]. In in vitro and in vivo iPSC experimental models, wide genomic instability has been detected, including chromosomal aberrations, copy number variations, and single nucleotide variations [8,9].…”
Section: Introductionmentioning
confidence: 99%